Hubungan hipertensi dengan kejadian presbikusis di Poliklinik THT-KL RSUP Sanglah Denpasar - Agus Santosa; Pande Ayu Naya Kasih Permatananda; I Putu Wirasatya Eka Putra (Intisari Sains Medis, 2022)
Introduction: Presbycusis or age-related hearing loss has several risk factors, with hypertension as one of them. Hypertension might cause presbycusis since it can interfere with nutrient and oxygen intake to the auditory nerve cells of the ear. This study aimed to determine the relationship between hypertension with the incidence of presbycusis at the Poliklinik THT-KL RSUP Sanglah Denpasar. Methods: This study used an analytic retrospective design and cross-sectional method. The study was conducted at the Poliklinik THT-KL RSUP Sanglah Denpasar with a sample of 60 people. Data were obtained using medical records and analyzed univariately and bivariate using SPSS for Windows with a p-value of 0.05. Results: Most subjects are 65-75 years old rather than >75, with male subjects of the same amount as female subjects. Chi-square test (x2) distribution table analysis demonstrated an association between hypertension and presbycusis incident in Poliklinik THT-KL RSUP Sanglah Denpasar with a p-value of 0,002. Conclusion: Most samples are in the 65-75 age range with the same proportionate amount of gender. There is an association between hypertension and presbycusis in Poliklinik THT-KL RSUP Sanglah Denpasar.   Latar Belakang: Presbikusis atau age related hearing loss memiliki beberapa faktor resiko dengan hipertensi sebagai salah satunya. Hipertensi dapat menyebabkan presbikusis karena dapat mengganggu asupan nutrisi dan oksigen sel-sel saraf auditori di telinga. Penelitian ini bertujuan mengidentifikasi hubungan hipertensi dan kejadian presbikusis di poliklinik Telinga, Hidung, Tenggorokan, Bedah Kepala dan Leher (THT-KL) RSUP Sanglah Denpasar. Metode: Desain yang digunakan yakni retrospektif analitik dan metode cross-sectional. Lokasi penenlitian yakni poliklinik THT-KL RSUP Sanglah Denpasar dan jumlah sampel 60 orang. Data diperoleh dengan menggunakan rekam medis dan dianalisis secara univariat dan bivariat melalui aplikasi SPSS dengan nilai p ≤ 0,05. Hasil: Didapatkan sampel lebih banyak berumur 65-75 tahun dibanding sampel berumur >75 tahun. Untuk jenis kelamin, ditemukan sampel dalam proporsi yang sama dan dari hasil uji chi square, didapat adanya korelasi antara hipertensi dengan kejadian presbikusis di Poliklinik THT-KL RSUP Sanglah Denpasar dengan nilai p = 0,002. Simpulan: Mayoritas sampel berumur 65-75 tahun dengan proporsi jenis kelamin yang sama. Diperoleh hubungan hipertensi dan kejadian presbikusis di poliklinik THT-KL RSUP Sanglah Denpasar.